PENGARUH MODEL PEMBELAJARAN MEANS ENDS ANALYSIS TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK KELAS VIII SMPN 1 PAYAKUMBUH - Putri, Regita Asmarani (Departemen Matematika, 2024)
Learning to solve problems effectively is the main reason why people learn maths. Actually, though, this is still significantly below than the standard that students have come to expect. One approach to making the most of this potential is the Means Ends Analysis learning paradigm. This research set out to evaluate the efficacy of two distinct approaches to teaching number patterns to eighth graders at SMPN 1 Payakumbuh: the conventional wisdom model and the more modern Means Ends Analysis model. The research utilized a control group design that solely included posttests. Results showed that eighth graders at SMPN 1 Payakumbuh made more progress using the MEA model than with the old model.Keywords– Means Ends Analysis,Mathematical Problem Solving, Conventional